IODP Expedition 361 Titration - Hall, I.R.; Hemming, S.R.; LeVay, L.J.; Barker, S.; Berke, M.A.; Brentegani, L.; Caley, T.; Cartagena-Sierra, A.; Charles, C.D.; Coenen, J.J.; Crespin, J.G.; Franzese, A.M.; et al. (Zenodo, 2020)
Various chemical constituents (most commonly chloride) were measured by titration using either an autotitrator (chloride) or a manual titrator (other compounds). Chloride was measured by ion-selective electrode and a silver nitrate titration until all chloride is bound as silver chloride.